Construction of Jodang Trap Wall - Gondo Puspito (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2010)
Fifty four jodang traps were operated in Palabuhanratu bay waters from November to December 2009. The objective was to get construction of jodang trap wall that productive and selective to catch mature babylon snails with shell length of p ≥ 4.27 cm. Slopes of trap wall were 30o, 40o and 50o. While, their meshes were 1.2 mm; 5.4 mm and 7.0 mm. Fishing operations were done 12 times with 3 hours soaking time for each fishing operation. Result showed that slopes of 30o and 40o with all meshes did not give significant change in number of mature snail catch. Construction of trap wall with slope of 50o and mesh of 5.4 mm was more productive and selective than those other contructions. Key Word : Wall Construction, Jodang Trap, Slope, Mesh and Babylon Snail.